2010
DOI: 10.5194/bg-7-2613-2010
|View full text |Cite
|
Sign up to set email alerts
|

Ballast minerals and the sinking carbon flux in the ocean: carbon-specific respiration rates and sinking velocity of marine snow aggregates

Abstract: Abstract.Recent observations have shown that fluxes of ballast minerals (calcium carbonate, opal, and lithogenic material) and organic carbon fluxes are closely correlated in the bathypelagic zones of the ocean. Hence it has been hypothesized that incorporation of biogenic minerals within marine aggregates could either protect the organic matter from decomposition and/or increase the sinking velocity via ballasting of the aggregates. Here we present the first combined data on size, sinking velocity, carbon-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
224
7

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(253 citation statements)
references
References 55 publications
(88 reference statements)
22
224
7
Order By: Relevance
“…Our treatments encompassed three acidification scenarios and five concentrations of the clay illite contained in cylindrical 5 liter rolling tanks rotating at 1 rpm on a roller table. Tanks were incubated at 14uC in continuous darkness for 44 to 48 h. Solid body rotation was established within 3 h (Ploug et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Our treatments encompassed three acidification scenarios and five concentrations of the clay illite contained in cylindrical 5 liter rolling tanks rotating at 1 rpm on a roller table. Tanks were incubated at 14uC in continuous darkness for 44 to 48 h. Solid body rotation was established within 3 h (Ploug et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…However, as pointed out by Richardson and Jackson (2007), export efficiency of small plankton cells is likely greater than thought and can be enhanced by aggregation processes which could act as trophic lifts. Moreover, recent experiments comparing the effect of the incorporation of biogenic minerals from different sources into marine aggregates on their decomposition and sinking velocities have shown that ballasting by carbonate increased sinking velocities and reduced respiration rate compared to aggregates ballasted by opal (Iversen and Ploug, 2010). Leblanc et al (2009) suggested sedimentation of diatoms in the form of aggregates based on the correspondence between TEP and biogenic silica at depth, while they also observed TEP associated with prymnesiophytes in the surface layer.…”
Section: Implications Of Phytoplankton Community Structure For Carbonmentioning
confidence: 99%
“…Therefore, as reported before Leblanc et al, 2009), PIC concentration is probably not a good indicator of in situ coccolithophore biomass but rather is an accumulative signal of present and prior calcification activity on short temporal time scale. This temporal decoupling is further complicated by TEP-mediated aggregation of coccoliths or their incorporation into faecal pellets after grazing, promoting the rapid disappearance of high reflectance remote sensing patches and potentially enhancing carbon export efficiency due to increased sinking velocity (De La Rocha and Passow, 2007;Harlay et al, 2009;Iversen and Ploug, 2010).…”
Section: Implications Of Phytoplankton Community Structure For Carbonmentioning
confidence: 99%
“…( and ) Sinking POC is a component of marine snow (marsnow) and as such is respired by heterotrophic bacteria (bacterial respiration, BR) at a rate of = 0.13 −1 (Iversen and Ploug, 2010). Sinking rates ( ) of organic material from PP and SP were adopted from Turner (2002) SP carcasses are assumed equivalent to detritus entangled in sinking marine snow and respired as such (Iversen and Ploug, 2010;Tang and Elliott, 2013).…”
Section: _66mentioning
confidence: 99%
“…Sinking rates ( ) of organic material from PP and SP were adopted from Turner (2002) SP carcasses are assumed equivalent to detritus entangled in sinking marine snow and respired as such (Iversen and Ploug, 2010;Tang and Elliott, 2013). We assumed a consumption rate similar to that of sinking faecal pellets ( _ , from Eq.…”
Section: _66mentioning
confidence: 99%